Jig and Fixture Redesign for Making Reamer on Head Cylinder - Tjiptady, Bella Cornelia; Rahman, Rifki Zainur; Meditama, Ratna Fajarwati; Widayana, Gede (Jurnal Pendidikan Teknik Mesin Undiksha, 2021)
Proses produksi telah banyak berevolusi dengan diperkenalkannya konsep manufaktur inovatif yang handal. Salah satu komponen mesin yang banyak diproduksi adalah cylinder head. Cylinder head harus tahan terhadap temperatur dan tekanan yang tinggi selama engine bekerja. Oleh sebab itu umumnya cylinder head dibuat dari besi tuang. Kendala yang ada saat ini yaitu proses pembuatan cylinder head kurang efektif dan efisien karena ketika menetapkan sudut untuk membuat reamer berbasis manual, selain itu setting benda kerja tidak otomatis sehingga membutuhkan waktu yang terlalu lama. Solusi dari permasalahan tersebut yaitu dengan adanya jig dan fixture. Metode penelitian yang digunakan adalah metodologi perancangan fixture (Society of Manufacturing Engineers). Berdasarkan hasil analisis, terdapat kelebihan dari jig dan fixture yang telah dirancang ulang yaitu: 1) memiliki stoper yang berfungsi untuk memberhentikan benda kerja, dengan sudut yang sudah ditentukan sehingga tidak perlu mensetting sudut kembali; 2) tidak mudah bergeser apabila fixture dipasang dan sejajar di meja frais; 3) terdapat dua engsel sehingga lebih balance; 4) pemasangan tidak rumit sehingga tidak memakan banyak waktu dalam pembuatan produk.Kata kunci: Jig and fixture; redesign; head cylinder The production process has evolved a lot with the introduction of innovative reliable manufacturing concepts. One of the engine components that are widely produced is the cylinder head. The cylinder head must withstand high temperatures and pressures while the engine is running. Therefore, generally the cylinder head is made of cast iron. The current constraint is that the cylinder head manufacturing process is less effective and efficient because when setting the angle to make the reamer a manual basis, besides that the workpiece setting is not automatic so it takes too long. The solution to this problem is the presence of jigs and fixtures. The research method used is the fixture design methodology (Society of Manufacturing Engineers). Based on the results of the analysis, there are advantages to the redesigned jig and fixture, namely: 1) it has a stoper which functions to stop the workpiece, at a predetermined angle so that there is no need to set the angle again; 2) it does not move easily when the fixture is installed and parallel to the milling table; 3) there are two hinges so that it is more balanced; 4) installation is not complicated so it does not take much time to manufacture the product.Keywords : Jig and fixture; redesign; head cylinder.  DAFTAR RUJUKAN Basuki, B., Yoto., Suyetno A., & Tjiptady, B. C. (2020). Management Model of Manufacturing Workshop/Laboratory of Vocational Education in the Industry 4.0. 4th International Conference on Vocational Education and Training (ICOVET), Malang, Indonesia, 2020, pp. 127-130, doi: 10.1109/ICOVET50258.2020.9230188. Choong, G. Y. H., Canciani, A., & Defocatiis, D. S. A. (2020). An Adaptable Flexural Test Fixture for Miniaturised Polymer Specimens. Polymer Testing, 85, 106430. doi:10.1016/j.polymertesting.2020.106430 Craig, O., Picavea, J., Gameros, A., Axinte, D., & Lowth, S. (2020). Conformable Fixture Systems With Flexure Pins For Improved Workpiece Damping. Journal of Manufacturing Processes, 50, 638–652. doi:10.1016/j.jmapro.2019.12.045  Fonte, M., Reis, L., Infante, V., & Freitas, M. (2019). Failure Analysis of Cylinder Head Studs of a Four Stroke Marine Diesel Engine. Engineering Failure Analysis. doi:10.1016/j.engfailanal.2019.03.026  Gameros, A., Lowth, S., Axinte, D., Nagy-Sochacki, A., Craig, O., & Siller, H. R. (2017). State-Of-The-Art In Fixture Systems For The Manufacture And Assembly Of Rigid Components: A Review. International Journal of Machine Tools and Manufacture, 123, 1–21. doi:10.1016/j.ijmachtools.2017.07.004 Jing, G. X., Zhang, M. X., Qu, S., Pang, J. C., Fu, C. M., Dong, C., Zhang, Z. F. (2018). Investigation into diesel engine cylinder head failure. Engineering Failure Analysis, 90, 36–46. doi:10.1016/j.engfailanal.2018.03.008  Kamble, V. D., & Mathew, A. T. (2020). Brief Review of Methodologies for Creation of Cohesive Fixture Design. Materials Today: Proceedings, 22, 3353–3363. doi:10.1016/j.matpr.2020.04.285  Kampker, A., Bergweiler, G., Hollah, A., Lichtenthäler, K., & Leimbrink, S. (2019). Design and Testing of The Different Interfaces In A 3D Printed Welding Jig. Procedia CIRP, 81, 45–50. doi:10.1016/j.procir.2019.03.009  Krznar, N., Pilipović, A., & Šercer, M. (2016). Additive Manufacturing of Fixture for Automated 3D Scanning–Case Study. Procedia Engineering, 149, 197–202. doi:10.1016/j.proeng.2016.06.656  Kumar, S., Campilho, R. D. S. G., & Silva, F. J. G. (2019). Rethinking Modular Jigs’ Design Regarding the Optimization of Machining Times. Procedia Manufacturing, 38, 876–883. doi:10.1016/j.promfg.2020.01.169 Lu, R., Li, Y.-C., Li, Y., Jiang, J., & Ding, Y. (2020). Multi-agent Deep Reinforcement Learning Based Demand Response for Discrete Manufacturing Systems Energy Management. Applied Energy, 276, 115473. doi:10.1016/j.apenergy.2020.115473  Ma, S., Zhang, Y., Yang, H., Lv, J., Ren, S., & Liu, Y. (2020). Data-driven Sustainable Intelligent Manufacturing Based on Demand Response for Energy-Intensive Industries. Journal of Cleaner Production, 123155. doi:10.1016/j.jclepro.2020. 123155 Marsono, Yoto, Sutadji E., & Tjiptady, B. C. (2020). Career Development and Self-Efficacy Through Industrial Working Practice in Vocational Education," 4th International Conference on Vocational Education and Training (ICOVET), Malang, Indonesia, 2020, pp. 1-4, doi: 10.1109/ICOVET50258.2020.9230111 Nee, A. Y. C., Bhattacharyya, N., & Poo, A. N. (1987). Applying AI in Jigs and Fixtures Design. Robotics and Computer-Integrated Manufacturing, 3(2), 195–200. doi:10.1016/0736-5845(87)90102-5 Qolik, A., Nurmalasari, R., Yoto., & Tjiptady, B. C. (2020). The Role of Special Job Fair in Distributing Competitive Graduates in the 21st Century. 4th International Conference on Vocational Education and Training (ICOVET), Malang, Indonesia, 2020, pp. 115-118, doi: 10.1109/ICOVET50258.2020.9230064 Schuh, G., Bergweiler, G., Lichtenthäler, K., Fiedler, F., & Puente, R. S. (2020). Topology Optimisation and Metal Based Additive Manufacturing of Welding Jig Elements. Procedia CIRP, 93, 62–67. doi:10.1016/j.procir.2020.04.066  Seloane, W. T., Mpofu, K., Ramatsetse, B. I., & Modungwa, D. (2020). Conceptual Design of Intelligent Reconfigurable Welding Fixture for Rail Car Manufacturing Industry. Procedia CIRP, 91, 583–593. doi:10.1016/j.procir.2020.02.217 Siva, R., Siddardha, B., Yuvaraja, S., & Karthikeyan, P. (2020). Improving the productivity and tool life by fixture modification and renishaw probe technique. Materials Today: Proceedings, 24, 782–787. doi:10.1016/j.matpr.2020.04.386  Tjiptady, B. C., Rohman, M., Sudjimat, D. A., Ratnawati, D. (2020). Analisis Tegangan, Deformasi, dan Retak Pada Gas Turbine Blade dengan Metode Elemen Hingga. Jurnal Taman Vokasi. Vol 8, (2). doi : 10.30738/jtv.v8i2.8425 Tjiptady, B. C., Yoto., & Marsono. (2020). Entrepreneurship Development Design based on Teaching Factory to Improve the Vocational Education Quality in Singapore and Indonesia, 4th International Conference on Vocational Education and Training (ICOVET), Malang, Indonesia, pp. 130-134, doi: 10.1109/ICOVET50258.2020.9230222 Tohidi, H., & Algeddawy, T. (2016). Planning of Modular Fixtures in a Robotic Assembly System. Procedia CIRP, 41, 252–257. doi:10.1016/j.procir.2015.12.090 Vijaya, R. B., Elanchezhian, C., Rajesh, S., Jaya, P. S., Kumaar, B. M., & Rajeshkannan, K. (2018). Design and Development of Milling Fixture for Friction Stir Welding. Materials Today: Proceedings, 5(1), 1832–1838. doi:10.1016/j.matpr.2017.11.282